2019
DOI: 10.1007/s42452-019-1849-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of wire electrical discharge machining using statistical methods coupled with artificial intelligence techniques and soft computing

Abstract: Wire electrical discharge machining (WEDM) is a special form of electrical discharge machining that uses a small diameter wire as the electrode to cut a narrow kerf in the workpiece. Although it is a simple concept, the performance of the process is highly dependent on the operating parameters. The aim of this work is to optimize WEDM operating parameters with the objective of achieving a maximum material removal rate (MRR) and minimum surface roughness (SR) for an AISI 304 stainless steel workpiece. This work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The WS 2 microparticles appear in the form of a blue-grey powder. The powder consists of Tungsten (74.13%) and Sulphur (25.87%) having a density of 7.5 g/cm 3 ; melting point 1250 °C; particle size 4-5 μm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WS 2 microparticles appear in the form of a blue-grey powder. The powder consists of Tungsten (74.13%) and Sulphur (25.87%) having a density of 7.5 g/cm 3 ; melting point 1250 °C; particle size 4-5 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The electric discharge or spark erosion for cutting takes place under the blanket of dielectrics such as mineral oil or kerosene fed to the container in which EDM takes place. The removed particles are getting flushed away with dielectric fluid flow [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of machining process parameters is also an essential and challenging task to obtain the best possible machinability, specially when machine DTM materials using advanced machining processes [15][16][17]. As regards to that review of some past literature on optimization of EDM and wire-EDM parameters for DTM materials, using hybrid intelligent techniques, has been done [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum values of responses were 4.0125 mm 3 /min MRR, 0.00012 gm/min tool wear rate, and 2.28 µm surface roughness. El-Bahloul [22] conducted research work on optimization of wire-EDM parameters using statistical method integrated with Fuzzy and successfully improved WEDM productivity and surface quality of 304 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…Mean roughness depth of 6.2 µm and 0.021 g/min material removal rate have been achieved after machining at optimum parameters produced by hybrid optimization technique. In an another important study, El-Bahloul [15] successfully improved process performance and stainless steel 304 part quality using response surface technique integrated Fuzzy approach. The research work reported by Tzeng et al [16] highlights the effectiveness of back-propagation neural network (BPNN), a genetic algorithm (GA), and response surface methodology (RSM) based hybrid technique for the WEDM parameter optimization to obtain better material removal rate (0.2704 g/ min) and average surface roughness (1.3561 µm) when machining tungsten carbide.…”
Section: Introductionmentioning
confidence: 99%